A kind of environmentally friendly liquid binder for refractory materials and preparation method thereof
By using a liquid bonding agent that combines calcium gallium molybdenum composite sol and its powder, the problem of degradation of the performance of existing bonding agents at high temperatures is solved, and the medium and high temperature strength and construction performance of the castable are improved.
Patent Information
- Application Number
- CN202410617498.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-05-17
AI Technical Summary
The performance of bonding agents in existing environmentally friendly refractory materials decreases at high temperatures, resulting in poor high-temperature performance of the castable, and the sol bonding agents used alone have shortcomings in construction performance and molding effect.
The liquid binding agent that combines calcium gallium-molybdenum composite sol and its powder is used to adjust the pH value and introduce complexing agents such as sodium polyacrylate and triamine citrate to form a stable solid-liquid blending state, which improves the high temperature strength and construction performance of the castable.
The medium and high temperature strength and volume stability of the castable material are improved, the construction performance and flowability are enhanced, and the existing binding agents are solved.
Smart Images

Figure CN118530033B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sol preparation for environmentally friendly refractory materials, and specifically refers to a liquid binder for environmentally friendly refractory materials and a preparation method thereof. Background Art
[0002] In the environmentally friendly refractory industry, aluminate cement bonded castables have the advantages of high early strength and good rheological properties, and are the most widely used binder in castables. However, cement will generate a low melting point phase at high temperatures, which will cause the high temperature performance of the castable to decrease, limiting the application range of the castable. At the same time, the study found that compared with aluminate cement, sol-bonded castables have obvious advantages in baking performance, thermal shock resistance, slag resistance, high temperature strength, etc.
[0003] Nowadays, amorphous refractories account for an increasingly higher proportion in the environmentally friendly refractory industry worldwide, and the development of binders is a key factor in the breakthrough progress of amorphous refractories. Some of the binders currently used in refractory castables mainly include silica sol, aluminate cement, etc., and the use of silica sol and aluminate cement inevitably introduces some impurities, which will produce some low melting phases after high-temperature heat treatment, resulting in poor high-temperature performance of the castable. Other sols, such as pure aluminum sol, have the disadvantages of low curing strength and poor construction performance when combined with corundum castables. Therefore, it is imperative to design and develop a sol with excellent performance for environmentally friendly refractory materials. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides an environmentally friendly liquid binder for refractory materials:
[0005] The liquid binder is in a solid-liquid mixed state and consists of a calcium-gallium-molybdenum composite sol, a calcium-gallium-molybdenum composite sol powder and a complexing agent;
[0006] The calcium-gallium-molybdenum composite sol in the liquid binder is obtained by using calcium nitrate as a calcium oxide precursor and gallium nitrate as a gallium oxide precursor, adjusting the pH value to form a calcium-gallium spinel precursor sol and then introducing the molybdenum element;
[0007] The complexing agents introduced into the liquid binder are sodium polyacrylate and triamine citrate.
[0008] Preferably, the pH value of the calcium gallium spinel precursor sol is 3-5; the addition amount of sodium polyacrylate in the complexing agent is 1-3 mg / mL, and the addition amount of triammine citrate is 8-10 mg / mL; the calcium gallium molybdenum composite sol powder in the liquid binder accounts for 1.5% of the total mass.
[0009] In addition, the present invention also provides a method for preparing an environmentally friendly liquid binder for refractory materials, wherein the preparation of the calcium-gallium-molybdenum composite sol comprises the following steps:
[0010] S1. Weigh calcium nitrate, gallium nitrate, molybdenum nitrate and citric acid respectively, put them in a beaker, add water and stir evenly to prepare 1 mol / L calcium nitrate, 1 mol / L gallium nitrate, 1 mol / L molybdenum nitrate and 1 mol / L citric acid solutions;
[0011] S2. According to the stoichiometric ratio of calcium gallium spinel Ca:Ga=1:2, calcium nitrate and gallium nitrate solution are measured, and molybdenum nitrate is added in a manner that it replaces calcium nitrate, that is, molybdenum nitrate + calcium nitrate: gallium nitrate=1:2, wherein the amount of the substance replaced by molybdenum nitrate accounts for 35% of the original calcium nitrate, and citric acid solution is added in a ratio of nitrate ion to citric acid of 1:1 to prepare a calcium gallium molybdenum precursor solution;
[0012] S3. The calcium gallium molybdenum precursor solution is sealed, placed in a heat-collecting constant temperature heating magnetic stirrer, and stirred at 70° C. for 48 h to prepare a calcium gallium molybdenum composite sol.
[0013] Preferably, the preparation of the calcium-gallium-molybdenum composite sol powder comprises the following steps:
[0014] Ⅰ. Heat the calcium-gallium-molybdenum composite sol on a hot plate in a fume hood, open the fume hood to exhaust, until boiling, to obtain a viscous calcium-gallium-molybdenum composite sol;
[0015] Ⅱ. Place the viscous calcium-gallium-molybdenum composite sol in an oven at 110°C for 4 h to dry, grind it in a mortar, and calcine it in a resistance furnace at 800-1000°C. After calcination for 30 min, a calcium-gallium-molybdenum composite sol powder is obtained.
[0016] The beneficial effects achieved by the present invention are as follows:
[0017] The present invention uses calcium nitrate, gallium nitrate and molybdenum nitrate as raw materials, synthesizes and prepares a stable new ternary composite sol (calcium gallium molybdenum composite sol) through a simple water bath heating process, and makes the powder into powder and adds a small amount of it into the calcium gallium molybdenum composite sol, and then introduces complexing agents sodium polyacrylate and triammine citrate, and evenly stirs to obtain the liquid binder of the present invention.
[0018] The calcium gallium molybdenum composite sol of the present invention is crystalline after heat treatment to form calcium gallium spinel CaGa 2 O 4 , generating nano-CaGa 2 O 4The filling effect will make the castable particles more compact, which is beneficial to improve the medium and high temperature strength of the castable. In addition, due to the introduction of molybdenum, the crystallization temperature during sol heat treatment increases, which in turn causes the average grain size of calcium gallium spinel to increase after heat treatment, promoting the development of the crystal type.
[0019] The liquid binder of the present invention adds a small amount of calcium gallium molybdenum composite sol powder to the main calcium gallium molybdenum composite sol, and is applied to the castable to effectively improve the volume stability of the castable, thereby solving the problem that the castable performance deteriorates, the molding effect is poor or it is difficult to mold when a single sol liquid binder is applied to the castable.
[0020] The liquid binder of the present invention introduces sodium polyacrylate and triammonium citrate as complexing agents, and when applied to castables, its steric hindrance effect can effectively improve the fluidity of the castables and maintain the construction performance of the castables within 60 minutes. In addition, the compressive strength of the castables is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The synthetic route of the liquid binder of Example 1 and Example 2 of the present invention;
[0022] Figure 2 The XRD spectra of the calcium gallium molybdenum composite sols of Example 1, Example 2 and Comparative Example 1 of the present invention after calcination at 800° C. and 1000° C.;
[0023] Figure 3 The permanent linear change rate of the castable after the liquid binder of Example 1 and Comparative Example 2 of the present invention is used in the castable;
[0024] Figure 4 This is a flowability trend diagram of the castable after the liquid binder is used in the castable in Example 1, Example 2 and Comparative Example 3 of the present invention.
[0025] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0028] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0029] Example 1: An environmentally friendly liquid binder for refractory materials, characterized in that the liquid binder is in a solid-liquid mixed state, and is composed of calcium gallium molybdenum composite sol, calcium gallium molybdenum composite sol powder (calcium gallium molybdenum composite sol powder accounts for 1.5% of the total mass of the liquid binder) and 1 mg / mL sodium polyacrylate and 8 mg / mL triamine citrate. The specific configuration steps of the liquid binder in Example 1 of the present invention are as follows:
[0030] ① Weigh calcium nitrate, gallium nitrate, molybdenum nitrate and citric acid respectively and place them in a beaker, add water and stir evenly to prepare 1 mol / L calcium nitrate, 1 mol / L gallium nitrate, 1 mol / L molybdenum nitrate and 1 mol / L citric acid solutions;
[0031] ② According to the stoichiometric ratio of calcium gallium spinel Ca:Ga=1:2, calcium nitrate and gallium nitrate solution are measured, and molybdenum nitrate is added in the manner of replacing calcium nitrate, that is, molybdenum nitrate + calcium nitrate: gallium nitrate=1:2, wherein the amount of the substance replaced by molybdenum nitrate accounts for 35% of the original calcium nitrate, and citric acid solution is added in a ratio of nitrate ion to citric acid of 1:1 to prepare a calcium gallium molybdenum precursor solution;
[0032] ③ The calcium gallium molybdenum precursor solution was sealed and placed in a heat-collecting constant temperature heating magnetic stirrer, and stirred at 70°C for 48 h to prepare a calcium gallium molybdenum composite sol;
[0033] ④ Heat the calcium-gallium-molybdenum composite sol on an electric heating plate in a fume hood, open the fume hood to exhaust, until boiling, to obtain a viscous calcium-gallium-molybdenum composite sol;
[0034] ⑤ Place the viscous calcium gallium molybdenum composite sol in an oven at 110°C for 4 h to dry, grind it in a mortar, and calcine it in a resistance furnace at 800°C. After calcination for 30 min, a calcium gallium molybdenum composite sol powder is obtained;
[0035] ⑥ Take calcium gallium molybdenum composite sol, calcium gallium molybdenum composite sol powder, sodium polyacrylate and triammonium citrate in a beaker and stir evenly to obtain the liquid binder of Example 1 of the present invention. In the liquid binder of Example 1 of the present invention, the calcium gallium molybdenum composite sol powder accounts for 1.5% of the total mass, the addition amount of sodium polyacrylate is 1 mg / mL, and the addition amount of triammonium citrate is 8 mg / mL.
[0036] Example 2: An environmentally friendly liquid binder for refractory materials, characterized in that the liquid binder is in a solid-liquid mixed state, and is composed of calcium gallium molybdenum composite sol, calcium gallium molybdenum composite sol powder (calcium gallium molybdenum composite sol powder accounts for 1.5% of the total mass of the liquid binder) and 3 mg / mL sodium polyacrylate and 10 mg / mL triamine citrate. The specific configuration steps of the liquid binder in Example 2 of the present invention are as follows:
[0037] ① Weigh calcium nitrate, gallium nitrate, molybdenum nitrate and citric acid respectively and place them in a beaker, add water and stir evenly to prepare 1 mol / L calcium nitrate, 1 mol / L gallium nitrate, 1 mol / L molybdenum nitrate and 1 mol / L citric acid solutions;
[0038] ② According to the stoichiometric ratio of calcium gallium spinel Ca:Ga=1:2, calcium nitrate and gallium nitrate solution are measured, and molybdenum nitrate is added in the manner of replacing calcium nitrate, that is, molybdenum nitrate + calcium nitrate: gallium nitrate=1:2, wherein the amount of the substance replaced by molybdenum nitrate accounts for 35% of the original calcium nitrate, and citric acid solution is added in a ratio of nitrate ion to citric acid of 1:1 to prepare a calcium gallium molybdenum precursor solution;
[0039] ③ The calcium gallium molybdenum precursor solution was sealed and placed in a heat-collecting constant temperature heating magnetic stirrer, and stirred at 70°C for 48 h to prepare a calcium gallium molybdenum composite sol;
[0040] ④ Heat the calcium-gallium-molybdenum composite sol on an electric heating plate in a fume hood, open the fume hood to exhaust, until boiling, to obtain a viscous calcium-gallium-molybdenum composite sol;
[0041] ⑤ Place the viscous calcium gallium molybdenum composite sol in an oven at 110°C for 4 h to dry, grind it in a mortar, and calcine it in a resistance furnace at 1000°C. After calcination for 30 min, a calcium gallium molybdenum composite sol powder is obtained;
[0042] ⑥ Take calcium gallium molybdenum composite sol, calcium gallium molybdenum composite sol powder, sodium polyacrylate and triammonium citrate in a beaker and stir evenly to obtain the liquid binder of Example 2 of the present invention. In the liquid binder of Example 2 of the present invention, the calcium gallium molybdenum composite sol powder accounts for 1.5% of the total mass, the addition amount of sodium polyacrylate is 3 mg / mL, and the addition amount of triammonium citrate is 10 mg / mL.
[0043] Comparative Example 1: The liquid binder of Comparative Example 1 of the present invention is divided into two groups. The calcination temperatures of the calcium gallium molybdenum composite sols in the two groups of liquid binders are 800°C and 1000°C, respectively, and no molybdenum element is introduced into the calcium gallium molybdenum composite sols in the two groups of liquid binders. Apart from these, the proportions of other ingredients and the preparation process are the same as those in Examples 1 and 2.
[0044] Comparative Example 2: The liquid binder of Comparative Example 2 of the present invention is different from the liquid binders of Examples 1 and 2 in that calcium gallium molybdenum composite sol powder is not introduced. Other than that, the proportions of other ingredients and the preparation process are the same as those of Examples 1 and 2.
[0045] Comparative Example 3: The liquid binder of Comparative Example 3 of the present invention is different from the liquid binders of Examples 1 and 2 in that the complexing agents sodium polyacrylate and triammonium citrate are not introduced. Apart from this, the proportions of other ingredients and the preparation process are the same as those of Examples 1 and 2.
[0046] Experimental example:
[0047] 1. Example 1, Example 2 and Comparative Example 1 of the present invention use an X-Pert Pro X-ray diffractometer to analyze the phase composition of the solid powder after the sol is heat-treated. The specific determination method is: the samples treated at different temperatures are ground into powders of about 40 μm, placed in the glass groove of the slide, flattened and compacted, and analyzed and measured in the diffractometer. The 2θ angle is set at 10° ~ 90°, the sample position remains unchanged during the scanning process, and the X-ray tube and the detector rotate relative to the sample for continuous scanning.
[0048] 2. The specific test method of the permanent line change rate of Example 1 and Comparative Example 2 of the present invention is as follows: after dry mixing and wet mixing, the casting slurry is placed in a mold with a size of 160 mm×40 mm×40 mm for vibration molding. After curing and demoulding, the distance between the two opposite surfaces before and after heating and insulation is measured with a vernier caliper along the length direction. A total of 4 points are measured and data are recorded. The permanent line change rate L c According to the formula (L c = (L 1 – L 0 ) / L 0 ) calculation, where L 0 Indicates the length value measured at each point before the spline is heated, L 1 Indicates the length value measured at each point after the spline is heated.
[0049] Result analysis:
[0050] Figure 1 This is a synthetic route map of the liquid binder of Example 1 and Example 2 of the present invention.
[0051] Figure 2The XRD patterns of the calcium gallium molybdenum composite sols of Example 1, Example 2 and Comparative Example 1 of the present invention after calcination at 800°C and 1000°C show that the half-peak width of the diffraction peak of the calcium gallium molybdenum composite sols of Example 1 and Example 2 is narrower than that of the calcium gallium molybdenum composite sol of Comparative Example 1 after calcination at 800°C and 1000°C. According to the Scherrer formula D=Kγ / βcosθ, the half-peak width of the diffraction peak in the XRD pattern is inversely proportional to the average size of the crystal, indicating that the average grain size of the calcium gallium spinel in the calcium gallium molybdenum composite sols of Example 1 and Example 2 at the same calcination temperature is larger, and the crystal development is more complete. The XRD analysis results show that the addition of molybdenum nitrate affects both the crystallinity and grain size of the calcium gallium spinel, reduces the crystallinity at the same temperature, and causes the spinel grains to grow abnormally.
[0052] Figure 3 The permanent linear change rate of the castable after the liquid binder of Example 1 and Comparative Example 2 of the present invention is used for the castable. It can be observed that after the liquid binder of Example 1 with the addition of calcium-gallium-molybdenum composite sol powder is used for the castable, the volume expansion rate of the castable at 110°C and 1100°C is smaller than that of Comparative Example 2. This is because the fluidity of the castable deteriorates after the addition of the sol powder, and the molding effect is not good. A large number of pores cannot be discharged during the molding process. The removal of moisture after drying has little effect on the increase in the total amount of pores in the castable, and the formation of a three-dimensional network skeleton after drying is also beneficial to maintaining the volume stability of the castable. Therefore, the volume expansion rate is reduced compared to when the sol powder is not added. In addition, the castable with the addition of sol powder even shrinks in volume at 1500°C, making the castable denser. The results of the permanent linear change analysis show that the introduction of part of the sol powder in the liquid binder is beneficial to the improvement of stability.
[0053] Figure 4 This is a trend diagram of the fluidity of the castable after the liquid binders of Example 1, Example 2 and Comparative Example 3 of the present invention are used in the castable. It can be observed that compared with the liquid binder of Comparative Example 3 without the addition of sodium polyacrylate and triamine citric acid complexing agent, the flow value of the castable is significantly increased after the liquid binders of Example 1 and Example 2 with the addition of sodium polyacrylate and triamine citric acid complexing agent are used in the castable. As time goes by, the fluidity of the castable also shows a trend of first increasing and then decreasing. Basically, the fluidity reaches the best at about 30 minutes, and can maintain good construction performance within 60 minutes. It can be seen that the introduction of sodium polyacrylate and triamine citric acid complexing agent has a certain dispersibility for the calcium gallium molybdenum composite sol-bonded castable, and the formed complex reduces the Ca in the castable slurry. 2+ Concentration, delaying hydration Ca(OH) 2 The crystallization process increases the fluidity of the castable.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0055] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. An environmentally friendly liquid binder for refractory materials, characterized in that: The liquid binder is in a solid-liquid mixed state and consists of a calcium-gallium-molybdenum composite sol, a calcium-gallium-molybdenum composite sol powder and a complexing agent; The calcium-gallium-molybdenum composite sol in the liquid binder is obtained by using calcium nitrate as a calcium oxide precursor and gallium nitrate as a gallium oxide precursor, adjusting the pH value to form a calcium-gallium spinel precursor sol and then introducing the molybdenum element; The complexing agents introduced into the liquid binder are sodium polyacrylate and triamine citrate; The preparation of the calcium gallium molybdenum composite sol powder comprises the following steps: Ⅰ. Heat the calcium-gallium-molybdenum composite sol on a hot plate in a fume hood, open the fume hood to exhaust, until boiling, to obtain a viscous calcium-gallium-molybdenum composite sol; II. Place the viscous calcium-gallium-molybdenum composite sol in an oven to dry, grind it in a mortar, and calcine it to obtain a calcium-gallium-molybdenum composite sol powder; The pH value of the calcium gallium spinel precursor sol is 3-5; the addition amount of sodium polyacrylate in the complexing agent is 1-3 mg / mL, and the addition amount of triammine citrate is 8-10 mg / mL; the calcium gallium molybdenum composite sol powder in the liquid binder accounts for 1.5% of the total mass.
2. A method for preparing the environmentally friendly liquid binder for refractory materials according to claim 1, characterized in that: The preparation of the calcium gallium molybdenum composite sol comprises the following steps: S1. Weigh calcium nitrate, gallium nitrate, molybdenum nitrate and citric acid respectively, put them in a beaker, add water and stir evenly to prepare 1 mol / L calcium nitrate, 1 mol / L gallium nitrate, 1 mol / L molybdenum nitrate and 1 mol / L citric acid solutions; S2. According to the stoichiometric ratio of calcium gallium spinel Ca:Ga=1:2, calcium nitrate solution and gallium nitrate solution are measured, molybdenum nitrate is added in the manner of replacing calcium nitrate, that is, molybdenum nitrate + calcium nitrate: gallium nitrate=1:2, wherein the amount of the substance replaced by molybdenum nitrate accounts for 35% of the original calcium nitrate, and citric acid solution is added in the ratio of nitrate ion to citric acid of 1:1 to prepare a calcium gallium molybdenum precursor solution; S3, sealing the calcium gallium molybdenum precursor solution, placing it in a heat-collecting constant temperature heating magnetic stirrer, and stirring to prepare a calcium gallium molybdenum composite sol.
Citation Information
Patent Citations
Regenerative iron runner castable
CN105218119A
Preparation and use method of refractory castable sol binder for kiln
CN115745440A